Green horizons: Using fodder crops to harness carbon and combat climate change - N. Sathiyabama; K. Sathiya Bama; R. Jayashree; R. K. Kaleeswari; K. N. Ganesan; R. Kalpana; R. Anandham (Plant Science Today, 2024)
Climate change, influenced by both natural processes and human activities, has notably transformed Earth's atmospheric composition, primarily due to heightened energy use in industrial and agricultural sectors. To combat this, a study was conducted focusing on soil management strategies, particularly using cumbu napier hybrid grass, to mitigate climate change by enhancing carbon sequestration. The research evaluated the effects of different nutrient sources including inorganic fertilizers, farmyard manure (FYM), poultry manure (PM) and biofertilizers like Arbuscular mycorrhiza (AM) and Azophos on greenhouse gas (GHG) emissions, soil carbon pools and soil organic carbon (SOC). The findings revealed that integrating organic manures with biofertilizers, particularly in the treatment involving PM at 75 % nitrogen equivalent combined with AM and Azophos (T10), significantly increased SOC levels (1.04 %) and lowered GHG emissions. This treatment also recorded the highest levels of soil inorganic carbon (0.131 %), passive carbon (7890 mg kg-1), permanent soil carbon stock (14.91 t ha-1 year-1), carbon pool index (1.37), carbon management index (201.1) and green fodder yield (370.2 t ha-1 year-1). On the other hand, the treatment with FYM alone at 100 % nitrogen equivalent (T7) resulted in the highest CO2 emissions (71.4 t ha-1 year-1), while the untreated control plot (T11) exhibited the highest global warming potential (GWP). This study underscores the effectiveness of strategic soil management in forage crop systems as a sustainable method to boost soil health, increase carbon sequestration and reduce GHG emissions, thus contributing to climate change mitigation.